Ultra-high-strength magnesium alloy and preparation method and application thereof
By optimizing the ratio of Li, Al, and Zn in magnesium alloys, and using process steps of smelting, homogenization treatment, hot extrusion and multi-pass rotary forging, the problem of insufficient strength of magnesium alloys is solved, and the tensile strength and specific strength are significantly improved.
Patent Information
- Application Number
- CN202410840893.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-26
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-06-26
AI Technical Summary
In the prior art, the tensile strength of magnesium alloys is generally less than 400MPa and the specific strength is less than 300kN·m/kg, making it difficult to meet the strength requirements of industrial applications.
Through the optimized ratio of alloy elements Li, Al, and Zn in the preparation method, including Li 4-6%, Al 1.5-2.5%, Zn 0.5-1.5% and the remaining Mg, the process steps such as smelting, homogenization treatment, hot extrusion and multi-pass rotary forging are carried out to control the grain size and deformation amount, and improve the strength of the magnesium alloy.
The tensile strength of the magnesium alloy reaches more than 500MPa, the specific strength reaches more than 300kN·m/kg, and has ultra-high strength.
Smart Images

Figure CN118813998B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of magnesium alloys, and in particular to an ultra-high strength magnesium alloy and a preparation method and application thereof. Background Art
[0002] Magnesium alloys have excellent damping properties, shock absorption, noise reduction and anti-electromagnetic interference properties, and have great application prospects in the automotive industry, communications electronics industry, aerospace industry and other fields. However, the low strength of magnesium alloys has greatly limited their industrial application.
[0003] In the prior art, the strength of magnesium alloys is often improved by changing the alloy composition or preparation process. For example, the invention patent with application number 201910784135.2 discloses a high-strength magnesium alloy and a preparation method thereof, and uses a variety of elements such as Li, Al, Zn, Ca, Mn, Zr, La and Ce to improve the performance of the magnesium alloy, and the resulting magnesium alloy has a tensile strength of 180 to 300 MPa; the invention patent with application number 201910784135.2 discloses a method for preparing a high-strength magnesium alloy by low-temperature rolling, and the resulting magnesium alloy has a tensile strength of 300 to 340 MPa; the invention patent with application number 201710090472.4 discloses a method for preparing a magnesium alloy by reciprocating warm rolling, and the resulting magnesium alloy has a tensile strength of less than 350 MPa; Yan Tang et al. published an article entitled "Influence of extruding In the article "Effects of extrusion temperature and heat treatment process on microstructure and mechanical properties of three structures containing Mg-Li alloy bars", a hot extrusion process for preparing magnesium alloy is introduced. The obtained magnesium alloy has a tensile strength of 329 MPa and a specific strength of 239 kN·m / kg. In summary, the tensile strength of magnesium alloys prepared by different methods in the prior art is generally lower than 400 MPa, and the specific strength is lower than 300 kN·m / kg.
[0004] Therefore, how to further improve the strength of magnesium alloys has become a difficult problem in the prior art. Summary of the invention
[0005] The purpose of the present invention is to provide an ultra-high strength magnesium alloy and its preparation method and application. The magnesium alloy prepared by the present invention has a tensile strength of more than 500 MPa and a specific strength of more than 300 kN·m / kg, and has ultra-high strength.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing an ultra-high-strength magnesium alloy, wherein the ultra-high-strength magnesium alloy comprises the following elements in percentage by mass: 4-6% Li, 1.5-2.5% Al, 0.5-1.5% Zn and the balance Mg; the total percentage by mass of the Al and Zn is ≤3%;
[0008] The method for preparing the ultra-high strength magnesium alloy comprises the following steps:
[0009] (1) smelting the alloy raw materials to obtain alloy ingots;
[0010] (2) subjecting the alloy ingot obtained in step (1) to homogenization treatment to obtain a homogenized alloy;
[0011] (3) hot extruding the homogenized alloy obtained in step (2) to obtain a magnesium alloy rod; the hot extrusion temperature is 150 to 250° C., and the extrusion ratio is 16 to 25;
[0012] (4) The magnesium alloy rod obtained in step (3) is subjected to multi-pass rotary forging to obtain an ultra-high strength magnesium alloy; the deformation amount of each pass of the multi-pass rotary forging is 1 to 6%; and the total deformation amount of the multi-pass rotary forging is 30 to 80%.
[0013] Preferably, the smelting temperature in step (1) is 650-750°C.
[0014] Preferably, the temperature of the homogenization treatment in step (2) is 260-300°C.
[0015] Preferably, the homogenization treatment time in step (2) is 10 to 15 hours.
[0016] Preferably, the homogenized alloy is preheated before hot extrusion in step (3).
[0017] Preferably, the preheating temperature is 150-250°C.
[0018] Preferably, the preheating time is 20 to 40 minutes.
[0019] The present invention provides an ultra-high strength magnesium alloy prepared by the preparation method described in the above technical solution.
[0020] The present invention also provides applications of the ultra-high strength magnesium alloy described in the above technical solution in the fields of automobiles, communications electronics and aerospace.
[0021] The present invention provides a method for preparing an ultra-high-strength magnesium alloy, wherein the ultra-high-strength magnesium alloy comprises the following elements in percentage by mass: 4-6% Li, 1.5-2.5% Al, 0.5-1.5% Zn and the remainder Mg; the total percentage by mass of the Al and Zn is ≤3%; the method for preparing the ultra-high-strength magnesium alloy comprises the following steps: (1) smelting an alloy raw material to obtain an alloy ingot; (2) homogenizing the alloy ingot obtained in the step (1) to obtain a homogenized alloy; (3) hot extruding the homogenized alloy obtained in the step (2) to obtain a magnesium alloy rod; the hot extrusion temperature is 150-250° C., and the extrusion ratio is 16-25; (4) performing multiple-pass rotary forging on the magnesium alloy rod obtained in the step (3) to obtain an ultra-high-strength magnesium alloy; the deformation amount of the multiple-pass rotary forging is 1-6%; and the total deformation amount of the multiple-pass rotary forging is 30-80%. The magnesium alloy provided by the present invention has a proper amount of Li, which reduces the weight of the magnesium alloy and improves the room temperature ductility. The proper amount of Al has a strong solid solution strengthening and aging strengthening effect, which improves the strength of the magnesium alloy. The proper amount of Zn improves the strength of the magnesium alloy through aging hardening. The alloy raw material is smelted and homogenized to make the alloy composition uniform. Then, hot extrusion is performed, and the extrusion temperature and extrusion ratio are controlled to reduce the grain size. Then, multiple passes of rotary forging are performed, and the deformation amount of each pass and the total deformation amount are controlled to make the core of the rod material deformed and penetrated, further refine the grains, and improve the strength of the magnesium alloy. The results of the embodiment show that the grain size of the magnesium alloy prepared by the present invention is below 100nm, the tensile strength reaches above 500MPa, and the specific strength reaches above 300kN·m / kg. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The alloy microstructure diagram of the ultra-high strength magnesium alloy prepared in Example 1 of the present invention;
[0023] Figure 2 The alloy microstructure diagram of the ultra-high strength magnesium alloy prepared in Example 2 of the present invention;
[0024] Figure 3 The alloy microstructure diagram of the ultra-high strength magnesium alloy prepared in Example 3 of the present invention;
[0025] Figure 4 The alloy microstructure diagram of the magnesium alloy prepared in Comparative Example 1 of the present invention;
[0026] Figure 5 This is the alloy microstructure diagram of the magnesium alloy prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0027] The present invention provides a method for preparing an ultra-high strength magnesium alloy, comprising the following steps:
[0028] (1) smelting the alloy raw materials to obtain alloy ingots;
[0029] (2) subjecting the alloy ingot obtained in step (1) to homogenization treatment to obtain a homogenized alloy;
[0030] (3) hot extruding the homogenized alloy obtained in step (2) to obtain a magnesium alloy rod;
[0031] (4) The magnesium alloy rod obtained in step (3) is subjected to multiple rotary forgings to obtain an ultra-high strength magnesium alloy.
[0032] In the present invention, the ultra-high strength magnesium alloy comprises the following elements in percentage by mass: Li 4-6%, Al 1.5-2.5%, Zn 0.5-1.5% and the balance Mg; the total percentage by mass of Al and Zn is ≤3%.
[0033] In the present invention, the ultra-high strength magnesium alloy includes 4-6% Li, preferably 4.5-5.5%, and more preferably 5% Li by mass percentage. In the present invention, the addition of Li can reduce the weight of the magnesium alloy, improve the room temperature ductility, and the addition of Li can also change the crystal structure of the magnesium alloy. The present invention limits the content of Li to the above range, which can adjust the structure of the magnesium-lithium alloy, improve the plasticity of the magnesium alloy, and will not cause over-aging precipitation in the alloy, and will not have a significant impact on its strength.
[0034] In the present invention, the ultra-high strength magnesium alloy includes 1.5-2.5% Al, preferably 2-2.5%, by mass percentage. In the present invention, the addition of the Al element improves the strength of the magnesium-lithium alloy, and has a strong solid solution strengthening and a certain aging strengthening effect. The present invention limits the Al content to the above range. When the Al content exceeds 3wt.%, MgAlLi2 and AlLi phases will be generated in the magnesium-lithium alloy, wherein the MgAlLi2 strengthening phase is easily transformed into the AlLi phase, which softens the alloy, and when Al exceeds a certain amount, it will cause micro-shrinkage of the cast structure, which will have an adverse effect on the mechanical properties.
[0035] In the present invention, the ultra-high strength magnesium alloy includes 0.5-1.5% Zn, preferably 1-1.5% Zn, in terms of mass percentage. In the present invention, the Zn has a good aging strengthening effect in Mg, and improves the strength of the alloy. The present invention limits the content of Zn to the above range. Adding an appropriate amount of Zn to the magnesium-lithium alloy can greatly improve the strength of the alloy through the effect of aging hardening, and has little effect on the plasticity and density of the alloy. However, adding a high content of Zn will not only greatly increase the density of the magnesium-lithium alloy, affecting the lightweight advantage of the magnesium-lithium alloy, but also reduce the stability of the organization and performance of the magnesium-lithium alloy due to the easy occurrence of over-aging.
[0036] In the present invention, the total mass percentage of Al and Zn is ≤3%, preferably 1-3%, more preferably 2-3%, and further preferably 2.5-2.9%. The present invention sets the total mass percentage of Al and Zn within the above range, which can refine the alloy grains and further improve the strength of the magnesium alloy.
[0037] In the present invention, the ultra-high strength magnesium alloy includes a balance of Mg in terms of mass percentage.
[0038] The invention melts alloy raw materials to obtain alloy ingots.
[0039] In the present invention, the alloy raw materials preferably include pure magnesium, pure lithium, pure aluminum and pure zinc; the purity of the pure magnesium, pure aluminum and pure zinc is preferably ≥99.9%, and the purity of the pure lithium is preferably ≥99.5%.
[0040] In the present invention, the smelting temperature is preferably 650-750°C, more preferably 680-720°C, and most preferably 700°C; the smelting time is preferably 60-120 min; and the smelting is preferably carried out under argon protection.
[0041] The present invention limits the parameters during smelting to the above ranges, which can make the alloy raw materials fully melted and further improve the performance of the alloy.
[0042] After smelting is completed, the present invention preferably cools the smelted product to obtain an alloy ingot.
[0043] The present invention has no special limitation on the cooling operation, and cooling to room temperature may be performed using cooling technical solutions well known to those skilled in the art.
[0044] After obtaining the alloy ingot, the present invention performs homogenization treatment on the alloy ingot to obtain a homogenized alloy.
[0045] In the present invention, the temperature of the homogenization treatment is preferably 260-300°C, more preferably 270-290°C, and further preferably 280°C; the time of the homogenization treatment is preferably 10-15h, more preferably 11-14h, and further preferably 12-13h; the homogenization treatment is preferably carried out under an argon atmosphere. The present invention limits the parameters of the homogenization treatment within the above ranges, which can make the alloy composition more uniform.
[0046] After the homogenization treatment is completed, the present invention preferably cools and mills the homogenized product in sequence to obtain a homogenized alloy.
[0047] In the present invention, the cooling is preferably air cooling.
[0048] The present invention has no special limitation on the operation of the milling surface, and the technical solution of milling surface well known to those skilled in the art can be adopted. In the present invention, the milling surface is used to remove the surface defects of the ingot.
[0049] After obtaining the homogenized alloy, the present invention performs hot extrusion on the homogenized alloy to obtain a magnesium alloy rod.
[0050] In the present invention, the homogenized alloy is preferably preheated before hot extrusion.
[0051] In the present invention, the preheating temperature is preferably the same as the hot extrusion temperature; the preheating time is preferably 20 to 40 minutes, more preferably 25 to 35 minutes, and further preferably 30 minutes. In the present invention, the preheating prevents the alloy from becoming coarse grains and cracking on the surface after extrusion.
[0052] In the present invention, the temperature of the hot extrusion is 150-250°C, preferably 180-220°C, and more preferably 200°C; the extrusion ratio during the hot extrusion is 16-25, preferably 18-22, and more preferably 20. In the present invention, dynamic recrystallization occurs in the alloy structure during the hot extrusion process, which can refine the grains and improve the alloy properties. The present invention limits the temperature and extrusion ratio of hot extrusion to the above range. If the extrusion temperature is too low, the grains of the bar will be fibrous, making it difficult to perform multiple rotary forgings. If the extrusion temperature is too high and the extrusion ratio is too low, the grain size of the bar will be too large.
[0053] After hot extrusion is completed, the present invention preferably cools the hot extruded product to obtain a magnesium alloy rod.
[0054] The present invention has no special limitation on the cooling operation, and any cooling technical solution well known to those skilled in the art may be used.
[0055] After obtaining the magnesium alloy rod, the present invention performs multiple-pass rotary forging on the magnesium alloy rod to obtain an ultra-high-strength magnesium alloy.
[0056] In the present invention, the temperature of the multi-pass rotary forging is preferably room temperature; the deformation of the multi-pass rotary forging is 1-6%, preferably 2-6%, more preferably 3-6%, and most preferably 4-5%; the total deformation of the multi-pass rotary forging is 30-80%, preferably 40-70%, and more preferably 50-60%. In the present invention, the rotary forging is used to refine the grains. The present invention limits the various parameters of the multi-pass rotary forging within the above range. If the deformation of the pass is too small, the core of the bar cannot be deformed and penetrated; if the deformation of the pass is too large, fracture is likely to occur; if the total deformation is too small, the grain refinement effect is insufficient, the alloy strength is low, and the total deformation is too large, fracture is likely to occur.
[0057] The present invention preferably replaces the rotary forging die with a finer hole diameter after every 3 to 5 rotary forging passes and continues rotary forging. The present invention replaces the rotary forging die with a finer hole diameter after every 3 to 5 rotary forging passes and continues rotary forging to ensure a stable strain rate and radial force, so that the forging frequency is consistent with the previous pass and a larger deformation amount is achieved.
[0058] The present invention preferably changes the feeding direction after each rotary forging to ensure the straightness of the bar.
[0059] In the magnesium alloy provided by the present invention, an appropriate amount of Li reduces the weight of the magnesium alloy and improves the room temperature ductility; an appropriate amount of Al has strong solid solution strengthening and aging strengthening effects and improves the strength of the magnesium alloy; and an appropriate amount of Zn improves the strength of the magnesium alloy through aging hardening; the alloy raw material is smelted and homogenized to make the alloy composition uniform; then hot extrusion is performed, and the extrusion temperature and extrusion ratio are controlled to reduce the grain size; then multiple passes of rotary forging are performed, and the deformation amount of each pass and the total deformation amount are controlled, so that the core of the rod is deformed and penetrated, the grains are further refined, and the strength of the magnesium alloy is improved.
[0060] The present invention provides an ultra-high strength magnesium alloy prepared by the preparation method described in the above technical solution.
[0061] The ultra-high strength magnesium alloy prepared by the present invention has higher strength.
[0062] The present invention also provides applications of the ultra-high strength magnesium alloy described in the above technical solution in the fields of automobiles, communications electronics and aerospace.
[0063] The present invention has no special limitation on the application of the ultra-high-strength magnesium alloy in the automotive, communications electronics and aerospace fields, and the technical solutions for the application of ultra-high-strength magnesium alloy in the automotive, communications electronics and aerospace fields well known to those skilled in the art may be adopted.
[0064] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0065] Example 1
[0066] The composition of the ultra-high strength magnesium alloy is as follows by mass percentage: Li: 4.4%, Al: 2.0%, Zn: 0.6% and the balance Mg;
[0067] The preparation method is:
[0068] (1) melting pure magnesium ingots (purity ≥ 99.9%), pure lithium ingots (purity ≥ 99.9%), pure aluminum ingots (purity ≥ 99.9%), and pure zinc ingots (purity ≥ 99.9%) in a vacuum melting furnace to obtain magnesium alloy ingots, the melting temperature is 700° C., the melting time is 60 min, and the melting is carried out under argon protection;
[0069] (2) performing a composition homogenization treatment under argon atmosphere protection, the homogenization temperature is 280° C., the homogenization time is 12 h, and after the homogenization treatment is completed, the ingot is air-cooled to room temperature, and then the surface defects of the ingot are removed by milling to obtain a homogenized alloy;
[0070] (3) preheating the homogenized alloy at 180° C. for 30 min, then hot extruding the alloy at a temperature of 180° C. and an extrusion ratio of 25, and cooling the alloy to obtain a magnesium alloy rod;
[0071] (4) The magnesium alloy rod was subjected to multiple passes of rotary forging at room temperature, with deformation amounts of 5.5%, 5.1%, 5.2%, 5.3%, 5.5%, 5.5%, 4.7%, 4.8% and 4.9% respectively. The feed direction was changed after each pass of rotary forging. After every three passes of rotary forging, a rotary forging die with a finer aperture was used to continue rotary forging. The total deformation amount was 38.2%, and an ultra-high strength magnesium alloy was obtained.
[0072] The alloy microstructure (transmission electron microscope bright field image) of the ultra-high strength magnesium alloy prepared in Example 1 is as follows Figure 1 As shown. Figure 1 It can be seen that the average grain size of the alloy is 95nm.
[0073] The tensile properties of the magnesium alloy prepared in Example 1 were tested according to GB / T16865-2013, and the yield strength was 463 MPa, the tensile strength was 519 MPa, the elongation after fracture was 12%, and the specific strength was 321 kN·m / kg.
[0074] Example 2
[0075] The composition of the ultra-high strength magnesium alloy is as follows by mass percentage: Li: 5.1%, Al: 2.4%, Zn: 0.5% and the balance Mg;
[0076] The preparation method is:
[0077] (1) melting pure magnesium ingots (purity ≥ 99.9%), pure lithium ingots (purity ≥ 99.9%), pure aluminum ingots (purity ≥ 99.9%), and pure zinc ingots (purity ≥ 99.9%) in a vacuum melting furnace to obtain magnesium alloy ingots, the melting temperature is 700° C., the melting time is 75 min, and the melting is carried out under argon protection;
[0078] (2) performing a composition homogenization treatment under argon atmosphere protection, the homogenization temperature is 280° C., the homogenization time is 12 h, and after the homogenization treatment is completed, the ingot is air-cooled to room temperature, and then the surface defects of the ingot are removed by milling to obtain a homogenized alloy;
[0079] (3) preheating the homogenized alloy at 170° C. for 30 min, then hot extruding the alloy at a temperature of 170° C. and an extrusion ratio of 16, and cooling the alloy to obtain a magnesium alloy rod;
[0080] (4) The magnesium alloy rod was subjected to multiple passes of rotary forging at room temperature, and the deformation amounts of each pass were 5.4%, 5.5%, 5.4%, 5.3%, 5.2%, 5.1%, 5.3%, 4.8%, 4.9%, 5.1%, and 5.2%, respectively. The feeding direction was changed after each pass of rotary forging. After every 4 passes of rotary forging, a rotary forging die with a finer aperture was used to continue rotary forging. The total deformation amount was 45.2%, and an ultra-high strength magnesium alloy was obtained.
[0081] The alloy microstructure (transmission electron microscope bright field image) of the ultra-high strength magnesium alloy prepared in Example 2 is as follows Figure 2 As shown. Figure 2 It can be seen that the average grain size of the alloy is 91nm.
[0082] The tensile properties of the magnesium alloy prepared in Example 2 were tested according to GB / T16865-2013, and the yield strength was 471 MPa, the tensile strength was 526 MPa, the elongation after fracture was 11%, and the specific strength was 333 kN·m / kg.
[0083] Example 3
[0084] The composition of the ultra-high strength magnesium alloy is as follows by mass percentage: Li: 4.9%, Al: 2.1%, Zn: 0.8% and the balance Mg;
[0085] The preparation method is:
[0086] (1) melting pure magnesium ingots (purity ≥ 99.9%), pure lithium ingots (purity ≥ 99.9%), pure aluminum ingots (purity ≥ 99.9%), and pure zinc ingots (purity ≥ 99.9%) in a vacuum melting furnace to obtain magnesium alloy ingots, the melting temperature is 700° C., the melting time is 120 min, and the melting is carried out under argon protection;
[0087] (2) performing a composition homogenization treatment under argon atmosphere protection, the homogenization temperature is 280° C., the homogenization time is 12 h, and after the homogenization treatment is completed, the ingot is air-cooled to room temperature, and then the surface defects of the ingot are removed by milling to obtain a homogenized alloy;
[0088] (3) preheating the homogenized alloy at 190° C. for 30 min, then hot extruding the alloy at a temperature of 190° C. and an extrusion ratio of 25, and cooling the alloy to obtain a magnesium alloy rod;
[0089] (4) The magnesium alloy rod is subjected to multiple passes of rotary forging at room temperature, and the deformation amounts of each pass are 5.5%, 5.3%, 5.4%, 5.1%, 4.6%, 4.7%, 4.8%, 3.7%, 3.8%, 3.9%, 3.3%, and 3.4%, respectively. The feeding direction is changed after each pass of rotary forging. After every 4 passes of rotary forging, a rotary forging die with a finer aperture is used to continue rotary forging. The total deformation amount is 42.7%, and an ultra-high strength magnesium alloy is obtained.
[0090] The alloy microstructure (transmission electron microscope bright field image) of the ultra-high strength magnesium alloy prepared in Example 3 is as follows Figure 3 As shown. Figure 3 It can be seen that the average grain size of the alloy is 92nm.
[0091] The tensile properties of the magnesium alloy prepared in Example 3 were tested according to GB / T16865-2013, and the yield strength was 476 MPa, the tensile strength was 521 MPa, the elongation after fracture was 11%, and the specific strength was 325 kN·m / kg.
[0092] Comparative Example 1
[0093] The magnesium alloy composition is as follows by mass percentage: Li: 5.1%, Al: 2.4%, Zn: 0.5% and the balance Mg;
[0094] The preparation method is:
[0095] (1) melting pure magnesium ingots (purity ≥ 99.9%), pure lithium ingots (purity ≥ 99.9%), pure aluminum ingots (purity ≥ 99.9%), and pure zinc ingots (purity ≥ 99.9%) in a vacuum melting furnace to obtain magnesium alloy ingots, the remainder of which is Mg and unavoidable impurities, the melting temperature is 700° C., and the melting time is 60 min;
[0096] (2) performing a composition homogenization treatment under argon atmosphere protection, the homogenization temperature is 280° C., the homogenization time is 12 h, and after the homogenization treatment is completed, the ingot is air-cooled to room temperature, and then the surface defects of the ingot are removed by milling to obtain a homogenized alloy;
[0097] (3) preheating the homogenized alloy at 170° C. for 30 min, then hot extruding the alloy at a temperature of 170° C. and an extrusion ratio of 16, and cooling the alloy to obtain a magnesium alloy rod;
[0098] (4) The magnesium alloy rod was subjected to multiple passes of rotary forging at room temperature, with deformation amounts of 5.9%, 5.6%, 5.8%, 5.6%, and 5.3% respectively. The feed direction was changed after each pass of rotary forging. After every 4 passes of rotary forging, a rotary forging die with a finer aperture was used to continue rotary forging. The total deformation amount was 25.2% to obtain a magnesium alloy.
[0099] The alloy microstructure (transmission electron microscope bright field image) of the magnesium alloy prepared in Comparative Example 1 is as follows Figure 4 As shown. Figure 4 It can be seen that due to the small total deformation, the grain refinement effect is insufficient and the alloy microstructure has not yet been refined into nanocrystalline.
[0100] The magnesium alloy prepared in Comparative Example 1 was subjected to a tensile property test according to GB / T16865-2013, and the yield strength was 368 MPa, the tensile strength was 421 MPa, the elongation after fracture was 11%, and the specific strength was 266 kN·m / kg.
[0101] Comparative Example 2
[0102] The magnesium alloy composition is as follows by mass percentage: Li: 4.9%, Al: 2.1%, Zn: 0.8% and the balance Mg;
[0103] The preparation method is:
[0104] (1) melting pure magnesium ingots (purity ≥ 99.9%), pure lithium ingots (purity ≥ 99.9%), pure aluminum ingots (purity ≥ 99.9%), and pure zinc ingots (purity ≥ 99.9%) in a vacuum melting furnace to obtain magnesium alloy ingots, the melting temperature is 700° C., the melting time is 75 min, and the melting is carried out under argon protection;
[0105] (2) performing a composition homogenization treatment under argon atmosphere protection, the homogenization temperature is 280° C., the homogenization time is 12 h, and after the homogenization treatment is completed, the ingot is air-cooled to room temperature, and then the surface defects of the ingot are removed by milling to obtain a homogenized alloy;
[0106] (3) preheating the homogenized alloy at 190° C. for 30 min, then hot extruding the alloy at a temperature of 190° C. and an extrusion ratio of 25, and cooling the alloy to obtain a magnesium alloy rod;
[0107] (4) The magnesium alloy rod is subjected to multiple passes of rotary forging at room temperature, with deformation amounts of 7.5%, 6.9%, 6.6%, and 6.5% respectively, and the feed direction is changed after each pass of rotary forging to obtain a magnesium alloy.
[0108] Due to the large deformation in each pass, the magnesium alloy bar cracked after the fourth rotary forging pass and could not be rotary forged further.
[0109] Comparative Example 3
[0110] The magnesium alloy composition is as follows by mass percentage: Li: 4.7%, Al: 3.1%, Zn: 1.0% and the balance Mg;
[0111] The preparation method is:
[0112] (1) melting pure magnesium ingots (purity ≥ 99.9%), pure lithium ingots (purity ≥ 99.9%), pure aluminum ingots (purity ≥ 99.9%), and pure zinc ingots (purity ≥ 99.9%) in a vacuum melting furnace to obtain magnesium alloy ingots, the melting temperature is 700° C., the melting time is 120 min, and the melting is carried out under argon protection;
[0113] (2) performing a composition homogenization treatment under argon atmosphere protection, the homogenization temperature is 280° C., the homogenization time is 12 h, and after the homogenization treatment is completed, the ingot is air-cooled to room temperature, and then the surface defects of the ingot are removed by milling to obtain a homogenized alloy;
[0114] (3) preheating the homogenized alloy at 190° C. for 30 min, then hot extruding the alloy at a temperature of 190° C. and an extrusion ratio of 25, and cooling the alloy to obtain a magnesium alloy rod;
[0115] (4) The magnesium alloy rod was subjected to multiple passes of rotary forging at room temperature, and the deformation amounts of each pass were 5.6%, 5.7%, 5.3%, 5.5%, 5.1%, 5.2%, 4.8%, 4.9%, 4.4%, 4.5%, 4.0% and 3.8%, respectively. The feeding direction was changed after each pass of rotary forging. After every 4 passes of rotary forging, a rotary forging die with a finer aperture was used to continue rotary forging. The total deformation amount was 45.3%, and a magnesium alloy was obtained.
[0116] The alloy microstructure (transmission electron microscope bright field image) of the magnesium alloy prepared in Comparative Example 3 is as follows Figure 5 As shown. Figure 5 It can be seen that the total mass percentage of Al and Zn alloy elements is 4.1%, which exceeds 3.0%. The alloy contains more second phases, and the final microstructure is lamellar and has not been refined into nanocrystalline.
[0117] According to GB / T16865-2013, the tensile properties of the magnesium alloy prepared in Comparative Example 3 were tested, and the yield strength was 415 MPa, the tensile strength was 463 MPa, the elongation after fracture was 12%, and the specific strength was 289 kN·m / kg.
[0118] In summary, the present invention controls the type and amount of alloy elements, the temperature of hot extrusion in the preparation process, the extrusion ratio, the deformation per pass and the total deformation during rotary forging to obtain an ultra-high strength magnesium alloy.
[0119] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an ultra-high strength magnesium alloy, wherein the ultra-high strength magnesium alloy comprises the following elements in percentage by mass: 4-6% Li, 1.5-2.5% Al, 0.5-1.5% Zn and the balance Mg; the total percentage by mass of Al and Zn is ≤3%; The method for preparing the ultra-high strength magnesium alloy comprises the following steps: (1) smelting the alloy raw materials to obtain alloy ingots; (2) subjecting the alloy ingot obtained in step (1) to homogenization treatment to obtain a homogenized alloy; (3) hot extruding the homogenized alloy obtained in step (2) to obtain a magnesium alloy rod; the hot extrusion temperature is 150 to 190° C., and the extrusion ratio is 16 to 25; (4) The magnesium alloy rod obtained in step (3) is subjected to multi-pass rotary forging at room temperature to obtain an ultra-high strength magnesium alloy; the deformation amount of the multi-pass rotary forging is 1 to 6%; and the total deformation amount of the multi-pass rotary forging is 30 to 80%.
2. The preparation method according to claim 1, characterized in that: The smelting temperature in step (1) is 650-750°C.
3. The preparation method according to claim 1, characterized in that: The temperature of the homogenization treatment in step (2) is 260-300°C.
4. The preparation method according to claim 1 or 3, characterized in that: The homogenization treatment time in step (2) is 10 to 15 hours.
5. The preparation method according to claim 1, characterized in that: In the step (3), the homogenized alloy is preheated before hot extrusion.
6. The preparation method according to claim 5, characterized in that: The preheating temperature is 150-250°C.
7. The preparation method according to claim 5 or 6, characterized in that: The preheating time is 20 to 40 minutes.
8. An ultra-high strength magnesium alloy prepared by the preparation method according to any one of claims 1 to 7.
9. Application of the ultra-high strength magnesium alloy according to claim 8 in the fields of automobiles, communication electronics and aerospace.
Citation Information
Patent Citations
High-strength ultra-light beta single-phase magnesium-lithium alloy plate and preparation method thereof
CN106834844A
Perovskite battery and nameplate with the same
CN110504364A
Preparation method of ultra-high-strength bulk nanometer magnesium alloy
CN108774723A
Preparing method of high-strength high-thermal-stability magnesium lithium alloy
CN111411276A